Effectiveness of Receivables Management in Increasing Sales Profit on Credit - Indah Wahyuning Tyas, Yayuk (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
This study aims to find out how the results of the analysis of the effectiveness of accounts receivable management in increasing profits through the implementation of policies on the sale of bags on credit at the Vion City Store Probolinggo, productive/profitable or ineffective/unprofitable. This type of research is descriptive research with quantitative methods—primary data sources in the form of interviews and secondary data that is financial statements. Data collection techniques used are observation and data documentation in Vion City Store Probolinggo. The percentage of profit from 2019 until 2019 always decreases to 27.79% in 2019 this is because the average receivables from 2019 to 2019 always increase. Hence, it affects the operating costs (investment), which has grown from the year 2019 until 2019.